Head and Neck Surgery: Clinical Updates and Perspectives - Locatello, Luca Giovanni; Gallo, Oreste (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
As Guest Editors, we are very delighted to see the reprint of our Special Issue, "Head and Neck Surgery: Clinical Updates and Perspectives", which is published in the Otolaryngology section of the Journal of Clinical Medicine. These papers are the joint effort of many excellent colleagues who have devoted their lives and careers to the exciting field of Otorhinolaryngology. As both clinicians and surgeons, we are actively advancing the diagnosis and management of the myriad of conditions affecting the head and neck region. Unprecedented discoveries in the field of genetics and molecular biology are always integrated with sound knowledge of the intricate anatomy of our discipline, while technological advancements now permit us to provide tailored and minimally invasive treatments for our patients. We wish to thank all the authors who contributed to this publication and we hope you enjoy reading it.